THE ONLY NON-CONTRADICTORY MODEL OF UNIVERSE - Skalsky, V. (Одеські астрономічні публікації, 2017)
The Friedmannian model of the flat expansive non-decelerative isotropic and homogeneous universe with the zero gravitational force state equation is the only model of universe, which does not contradict to the theory of relativity and the quantum mechanics.